2010
DOI: 10.1002/ceat.201000379
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Extraction of Chlorophyll a from Spirulina platensis with a Static Modifier

Abstract: Supercritical CO 2 extraction with a static modifier was applied to extract chlorophyll a from Spirulina platensis. The effects of the process were investigated by single-factor and response surface analysis experiments. The optimal process parameters for supercritical CO 2 extraction were determined to be: ethanol/water as the modifier, 40 vol.-% water content in the modifier, 21.2 mL modifier volume, 1 h static soaking time, 2 h dynamic extraction time, 48.7 MPa extraction pressure, 326.4 K extraction temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Their comparison experiments demonstrated that scCO 2 extraction with modifier was more efficient than conventional solvent methods. Their results are also in numerical agreement with the present work (their extraction yield was 6.84 mg g -1 ) 39 . Macías-Sánchez et al, recovered only low amount of chlorophylls, if compared to results obtained in this work, due to the absence of any modifier in the extraction process 40 .…”
Section: Sc-co 2 Extraction Of Chlorophyllssupporting
confidence: 92%
See 1 more Smart Citation
“…Their comparison experiments demonstrated that scCO 2 extraction with modifier was more efficient than conventional solvent methods. Their results are also in numerical agreement with the present work (their extraction yield was 6.84 mg g -1 ) 39 . Macías-Sánchez et al, recovered only low amount of chlorophylls, if compared to results obtained in this work, due to the absence of any modifier in the extraction process 40 .…”
Section: Sc-co 2 Extraction Of Chlorophyllssupporting
confidence: 92%
“…Nevertheless, only few investigations are available on the extraction of chlorophyll a using scCO 2 . Some works in the literature employed a co-solvent to enhance the supercritical fluid solvating power towards the molecule 39,40 . Carotenoids-free spirulina biomass underwent scCO 2 extraction with the addition of ethanol as co-solvent, to enhance the extraction yield towards more polar compounds.…”
Section: Sc-co 2 Extraction Of Chlorophyllsmentioning
confidence: 99%
“…Moreover, the elution pretreatment method makes it possible to achieve a 10-% selectivity of lutein, which is higher than that obtained with the previous method of Kitada et al [7] under the same extraction conditions. It can be explained that ethanol acts not only as an elution solvent but also as a solvent causing swelling of the C. vulgaris cell matrix during the soaking process [20] and enhancing the solubility of lutein in the SCCO 2 extraction process [7][8][9][10]. From this, it can be inferred that prolonging the soaking time [11] of C. vulgaris could assist the mass transfer of the SCCO 2 extraction process, resulting in an increase in the amount of lutein in the extract.…”
Section: Comparison Of Extraction Methodsmentioning
confidence: 94%
“…Although an economic and environmental analysis was not performed in this work, there are several indications of the environmentally friendly nature and economic viability of this process, namely, the reuse of the solvents in new cycles of extraction, 15,34 the multiproduct scenario represented by this process and the fact that this process employs an aqueous solution of an ammonium-based IL (representing the cheapest family 40 ) instead of a pure organic solvent. 40 Photosensitizing Potential of the Extracts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The assay suggests a SLR of 0.024 g dry biomass mL solvent –1 and a time of extraction of 43.9 min as optimal conditions. These conditions were experimentally tested in triplicate, and the maximum value of extraction was confirmed as being 3.50 ± 0.19 mg chl g dry biomass –1 , which is in agreement with the values previously published regarding the extraction of chlorophyll from Spirulina sp. , …”
Section: Results and Discussionmentioning
confidence: 99%